Remarkable Phytochemical Characteristics of Chi-Nan Agarwood Induced from New-Found Chi-Nan Germplasm of Aquilaria sinensis Compared with Ordinary Agarwood. (10th April 2021) - Yu, Meng; Liu, Yangyang; Feng, Jian; Chen, Deli; Yang, Yun; Liu, Peiwei; Yu, Zhangxin; Wei, Jianhe
Abstract : Wild Chi-Nan agarwood is regarded as the highest quality agarwood from Aquilaria spp. However, the comprehensive research on chemical composition of wild Chi-Nan agarwood is limited. An integrated strategy using SHS-GC-MS and UPLC-Q/Tof-MS was applied to explore the phytochemical characteristics of a kind of agarwood induced from a newly identified germplasm of Chi-Nan A. sinensis. Progenesis QI and MS-Dial were used to preprocess the UPLC-Q/Tof-MS and GC-MS raw data, respectively. Principle component analysis (PCA) and orthogonal partial least squares to latent structure-discriminant analysis (OPLS-DA) models were built to discriminate Chi-Nan agarwood from ordinary agarwood and to screen potential distinguishing components between them. In this study, we clarified the distinguishing differences between Chi-Nan agarwood and ordinary agarwood. The difference is mainly manifested in the average contents of 2-(2-phenylethyl)chromone and 2-[2-(4′-methoxybenzene)ethyl]chromone, which are 170 and 420 times higher in Chi-Nan agarwood than in ordinary agarwood, respectively, while the contents of 5, 6, 7, 8-diepoxy-2-(2-phenylethyl)chromones(DEPECs), 5, 6-epoxy-2-(2-phenylethyl)chromones(EPECs), and 5, 6, 7, 8-tetrahydro-2-(2-phenylethyl)chromones(THPECs) such as agarotetrol are extremely low. The content of the main sesquiterpenes in Chi-Nan agarwood was higher than that in ordinary agarwood, especially in regard to guaiane and eudesmane derivatives. In addition, there were significant differences in the contents of low-molecular-weight aromatic compounds such as 2-methyl-4H-1-benzopyran-4-one, 4-methoxybenzaldehyde, and 2-hydroxybenzaldehyde between Chi-Nan agarwood and ordinary agarwood. All the mentioned main chemical characteristics of this new Chi-Nan agarwood were coincident with those of the rare wild Chi-Nan agarwood from A. malaccensis, A. sinensis, and A. crassna . We reported differences in 2-(2-phenylethyl)chromones, sesquiterpenes, and low-molecular-weight aromatic compounds between Chi-Nan agarwood and ordinary agarwood from A. sinensis for the first time; it is necessary to evaluate the agarwood from the new-found Chi-Nan germplasm.